2015
DOI: 10.1155/2015/781380
|View full text |Cite
|
Sign up to set email alerts
|

On Tracking Dynamic Objects with Long Range Passive UHF RFID Using a Mobile Robot

Abstract: Service robots have shown an impressive potential in providing assistance and guidance in various environments, such as supermarkets, shopping malls, homes, airports, and libraries. Due to the low cost and contactless way of communication, radiofrequency identification (RFID) technology provides a solution to overcome the difficulties (e.g., occlusions) that the traditional line-of-sight sensors (e.g., cameras and laser range finders) face. In this paper, we address the applications of using passive ultrahigh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…By introducing RFID to the recycling process, it would be easier to identify which polymers are used in each garment and, by doing this, would effectively simplify the recycling process so unnecessary time and resources are not wasted in trying to recycle what is not recyclable. Furthermore, it has been shown that passive UHF (Ultra High Frequency) RFID tags have the ability to let the readers track the route of the garment through mobile platforms [41,42]. This can make recycling of garments more accessible by helping recycling facilities easily gauge the location of relevant items through an easy to use platform.…”
Section: Environmental Benefits Of the Rfid Technology In Apparel Indmentioning
confidence: 99%
“…By introducing RFID to the recycling process, it would be easier to identify which polymers are used in each garment and, by doing this, would effectively simplify the recycling process so unnecessary time and resources are not wasted in trying to recycle what is not recyclable. Furthermore, it has been shown that passive UHF (Ultra High Frequency) RFID tags have the ability to let the readers track the route of the garment through mobile platforms [41,42]. This can make recycling of garments more accessible by helping recycling facilities easily gauge the location of relevant items through an easy to use platform.…”
Section: Environmental Benefits Of the Rfid Technology In Apparel Indmentioning
confidence: 99%
“…The two stage dynamic motion model was combined with the dual particle filter in order to capture the dynamic motion of the object and to quickly recover from failures in tracking. And this approach was then tested on a Scitos G5 mobile robot through various experiments [4]. The researchers proposed a novel ubiquitous architecture followed by a protocol for tracking mobile objects in real-time based upon the RFID Tags [5] .An internet based concept incorporated with RFID technology was proposed to form an internet based application for the library management and the RFID reader Motorola MC9090 was used for the entire process which was carried inside the library [6].…”
Section: Imentioning
confidence: 99%
“…Due to its unique and contactless features of identification, RFID gradually becomes the preferred technology for indoor positioning. For example, Liu et al [8] [9] used RFID for the inventory of a library using a mobile robot. Xie et al [10] used RFID to create a smart bookshelf that provides automated and intelligent book management.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers also focused on dynamic objects tracking using RFID tags. Liu et al [8] [19] combined RFID and laser sensor to follow a dynamic RFID tag with obstacle avoidance capabilities using a mobile robot. Their algorithm combines two kinematics models and a dual particle filter to achieve fast tracking of dynamic RFID tags.…”
Section: Introductionmentioning
confidence: 99%